ANALYSIS OF LOCAL AREA NETWORK (LAN) UTILIZATION IN IMPROVING LOAN SERVICE ( Study at PT. Bank Rakyat Indonesia Tbk. Branch Malang, Kawi) - Yanuar Armansyah; Kertahadi Kertahadi; Riyadi Riyadi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2016)
The Purpose of this research is to know and to find out how utilization of LAN for loan service Study at PT. Bank Rakyat Indonesia Tbk. Branch Malang, Kawi. Type of this research can be considered as the explanatory research with the method of interview, documentation, and observation for collecting data methods. For data analysis is using data analysis spiral to analyze qualitative data, researcher engages in the process of moving in analytic circles rather than using a fixed linear approach. Based on the survey results revealed the LAN used at PT. Bank Rakyat Indonesia Tbk. Branch Malang, Kawi in loan service can more improving more then before no using LAN in loan service. The survey results revealed the LAN is used at PT. Bank Rakyat Indonesia Tbk. Branch Malang, Kawi in loan service is not maximized. Topology is tree topology can be replaced with a star topology, because the star topology has more advantages. Use of software and hardware that consumes less support in improving employee performance. Internet use at PT. Bank Rakyat Indonesia Tbk. Branch Malang, Kawi is less than maximum should implement an intranet to help information system to be more easly, smoothly and efficiently. Key words: Local Area Network (LAN) , Loan Service. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui dan mencari tahu bagaimana dari pemanfaatan LAN untuk layanan pinjaman Studi di PT. Bank Rakyat Indonesia Tbk. Cabang Malang, Kawi. Jenis penelitian ini dapat dianggap sebagai penelitian penjelasan dengan metode wawancara, dokumentasi, dan observasi untuk mengumpulkan metode data. Untuk analisis data menggunakan analisis data spiral untuk menganalisis data kualitatif, peneliti terlibat dalam proses bergerak dalam lingkaran analitik daripada menggunakan pendekatan linear tetap. Berdasarkan hasil survei mengungkapkan LAN digunakan di PT. Bank Rakyat Indonesia Tbk. Cabang Malang, Kawi dalam pelayanan pinjaman dapat lebih meningkatkan lebih sebelum ada menggunakan LAN dalam pelayanan pinjaman. Hasil survei mengungkapkan LAN digunakan pada PT. Bank Rakyat Indonesia Tbk. Cabang Malang, Kawi dalam pelayanan pinjaman belum maksimal. Topologi topologi pohon bisa diganti dengan topologi bintang, karena topologi star memiliki keunggulan lebih. Penggunaan perangkat lunak dan perangkat keras yang mengkonsumsi kurang mendukung dalam meningkatkan kinerja karyawan. penggunaan internet di PT. Bank Rakyat Indonesia Tbk. Cabang Malang, Kawi kurang maksimal harus menerapkan intranet untuk membantu sistem informasi menjadi lebih easly, lancar dan efisien. Kata Kunci : Pelayanan Pinjaman, Local Area Network (LAN).